2019
DOI: 10.1080/21505594.2019.1603133
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive proteomic analysis of exoproteins expressed by ERIC I, II, III and IVPaenibacillus larvaegenotypes reveals a wide range of virulence factors

Abstract: American foulbrood is a quarantine disease of the honeybee Apis mellifera L. in many countries and contributes greatly to colony losses. We performed a label-free proteomics study of exoprotein fractions produced in vitro by Paenibacillus larvae reference strains of the ERIC I–IV genotypes. A quantitative comparison was performed of previous studied protein-based virulence factors and many newly identified putative virulence factors. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(57 citation statements)
references
References 89 publications
10
45
2
Order By: Relevance
“…Four genotypes of P. larvae have been established using by mass spectrometry [ 39 ] and repetitive-element PCR analysis [ 40 , 41 ]. Primers specific to enterobacterial repetitive intergenic consensus (ERIC) sequences revealed four distinct banding patterns, resulting in the nomenclature of P. larvae ERIC I–IV.…”
Section: Introductionmentioning
confidence: 99%
“…Four genotypes of P. larvae have been established using by mass spectrometry [ 39 ] and repetitive-element PCR analysis [ 40 , 41 ]. Primers specific to enterobacterial repetitive intergenic consensus (ERIC) sequences revealed four distinct banding patterns, resulting in the nomenclature of P. larvae ERIC I–IV.…”
Section: Introductionmentioning
confidence: 99%
“…Epsilon toxins change the cell permeability for ions by forming large membrane pores, causing cell death and edema in animal models [67]. It was recently suggested that a protein of the ETX/MT2 family is an important virulence factor in two subtypes of P. larvae, the causative pathogen of American foulbrood [68]. It is thus plausible that melissotoxin A increases the virulence of M. plutonius by corrupting the cells of the larva's digestive tract.…”
Section: Role Of Melissotoxin a In Virulencementioning
confidence: 99%
“…Bacteria from this genus were also shown to produce a plethora of enzymes, like amylases, cellulases, hemicellulases, lipases, pectinases, oxygenases or dehydrogenases ( Grady et al, 2016 ). The proteome of P. larvae includes a wide range of virulence factors including proteases and toxins ( Erban et al, 2019 ). Paenibacillus validus stimulated the growth of Glomus intraradices ( Hildebrandt et al, 2006 ) and P. vortex facilitates dispersal of Aspergillus fumigatus ( Ingham et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%